Evaluasi Penentuan Kelayakan Pemberian Subsidi Listrik dengan Metode MFEP - Bobi Heri Yanto; Yuhandri Yunus (SAFE-Network, 2021)
The electricity subsidy program is a poverty control program that provides electricity subsidies to poor and underprivileged households that are paid by the Government of Indonesia to PT. PLN. The purpose of providing subsidies is to achieve a power supply and help poor customers and those who have not been contacted by PT. PLN so that they can enjoy electrical energy. At PT. Haleyora Power to determine the recipients of electricity subsidies there are still many mistakes such as not being on target, these subsidies are even obtained by people who are able to this incident not only in one period but often, because in the Decision Making System determining the eligibility of electricity subsidy recipients still uses a manual process and the database used is still in paper form in the form of files and there are no specific characteristics to be considered. This research aims to produce a system that can be used as a tool and makes it easier to determine the eligibility of electricity subsidy recipients. The method used in this research is the Multifactor Evaluation Process (MFEP) method. With the existence of a decision support system for determining eligibility assistance for electricity subsidies, the eligibility criteria will become clearer. The results of the ranking of 20 potential electricity subsidy recipients whose data are processed and produce a total calculation or accuracy of 100% using the Multifactor Evaluation Process (MFEP) method based on data on electricity subsidy recipients at PT. Haleyora Power. So that this research can be a reference in making the right decisions on providing electricity subsidies at PT. Haleyora Power.